High-stability liquid crystal display (LCD) filter film and preparation method thereof
By designing a filter film including a back coating, a lower base film, a light absorbing layer and a prism structural layer in an LCD display, the problem of inconvenience in color gamut improvement and assembly of traditional LCD displays is solved, and the effect of color gamut improvement, brightness enhancement and cost reduction is achieved.
Patent Information
- Application Number
- CN202510632418.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-07-22
AI Technical Summary
The color gamut improvement of traditional LCD displays faces challenges, and the multi-layer optical diaphragm stacking structure leads to inconvenience in assembly, reduced optical life of the diaphragm and poor peeling force of the film.
A high-stability filter film for LCD display is designed, including a back coating, a lower base film, a light absorbing layer, a lower prism structural layer and an upper base film. By adding a specific light absorber and a silane coupling agent to the light absorbing layer, combining the prism structural layer, the peeling force and optical life between the film layers are improved, and the brightness loss is compensated by a brightening film.
It improves the color gamut and light transmission of LCD monitors, extends the service life of the diaphragm, avoids poor picture problems, and reduces production costs.
Smart Images

Figure CN120352968A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor display, and particularly relates to a filter film for LCD display with high stability and a preparation method thereof. Background Art
[0002] Traditional liquid crystal displays (LCDs) mainly rely on the white light source emitted by the backlight module LED as the backlight source. After the white light source reaches the liquid crystal screen, it is then split into blue light, red light, and green light through a color filter film. However, because the spectra of the split red light and green light are continuous and have a relatively wide full width at half maximum, and the color purity is low, the color performance effect shown by traditional LCD displays is poor (low color gamut). However, low-end LCD displays are still the first choice for most consumers, with a market share of 80 - 90%. However, there are still important challenges in improving the color gamut of traditional LCD displays. Quantum dot optical films paired with GaN blue light as the backlight source of the LCM (LCD Module) can greatly improve the color gamut of LCD displays, and the NTSC color gamut can be increased from 70% to 95% - 120%. However, this also brings an increase in cost, and moreover, this strategy is not applicable in improving the color gamut of large-size low-end models with YAG (yttrium aluminum garnet) white light as the backlight source.
[0003] Currently, the color gamut of displays can be improved by two methods: adding functional optical films to the module architecture and optimizing the backlight source. By selecting materials with specific absorption bands, the excess spectral bands (485 - 510 nm, 580 - 610 nm) in the white light source are absorbed, reducing the color bleeding of red, green, and blue, and thus effectively improving the color purity of the transmitted light and shortening the full width at half maximum of the three-color light, thereby improving the color gamut of the display. However, the filtration of light is bound to cause a loss of brightness, and a single filter film does not have a brightness enhancement function. Therefore, the filter film must be used in conjunction with a brightness enhancement film. Currently, commonly used brightness enhancement films include prism films, prism composite films, reflective polarizing brightness enhancement films, etc. Among them, the prism composite film has the best brightness enhancement effect. However, the stacked structure of multiple optical film sheets will bring many inconveniences to end customers during the assembly of the entire unit. Integrating the dye that plays a filtering role with an optical composite film may simultaneously cause problems such as a reduction in the optical life of the film sheet and poor film layer peel strength.
[0004] Therefore, there is an urgent need to develop a new filter film for LCD display to solve the above problems. Summary of the Invention
[0005] Technical problem to be solved: In view of the above technical problems, the present invention provides a filter film for LCD display with high stability and a preparation method thereof, which can effectively solve the problems that the stacked structure of the above multi-layer optical film brings many inconveniences to the end customers during the whole machine assembly, as well as the problems such as the reduction of the optical life of the film and the poor peel strength of the film layer.
[0006] Technical solution: In a first aspect, the present invention provides a filter film for LCD display with high stability, including a back coating, a lower base film, a light absorption layer, a lower prism structure layer and an upper base film. When the light absorption layer is located on the upper surface of the lower base film, the structure of the filter film from bottom to top sequentially includes a back coating, a lower base film, a light absorption layer, a lower prism structure layer and an upper base film, and an upper prism structure layer or an upper lens structure layer is provided on the upper surface of the upper base film;
[0007] When the light absorption layer is located on the upper surface of the upper base film, the structure of the filter film from bottom to top sequentially includes a back coating, a lower base film, a lower prism structure layer, an upper base film and a light absorption layer, and an upper prism structure layer or an upper lens structure layer is provided on the upper surface of the light absorption layer.
[0008] Preferably, the filter film further includes a light diffusion layer, and the light diffusion layer is provided on the upper surface of the upper prism structure layer.
[0009] In a second aspect, the present invention provides a preparation method of a filter film for LCD display with high stability. When the light absorption layer is located on the upper surface of the lower base film, the preparation method of the filter film includes the following steps:
[0010] S1. Prepare the thermosetting glue for the light absorption layer;
[0011] S2. Introduce the light absorption layer on the lower base film with a back coating;
[0012] S3. Sequentially introduce the lower prism structure layer and the upper base film on the light absorption layer;
[0013] S4. Introduce the upper prism structure layer or the upper lens structure layer on the upper surface of the upper base film.
[0014] In a third aspect, the present invention provides a preparation method of a filter film for LCD display with high stability. When the light absorption layer is located on the upper surface of the upper base film, the preparation method of the filter film includes the following steps:
[0015] Step 1. Prepare the thermosetting glue for the light absorption layer;
[0016] Step 2. Sequentially introduce the lower prism structure layer and the upper base film on the lower base film with a back coating;
[0017] Step 3. Introduce the light absorption layer on the upper surface of the upper base film;
[0018] Step 4: Introduce an upper prism structure layer or an upper lens structure layer on the upper surface of the light absorption layer.
[0019] Fourthly, the present invention provides a method for preparing a filter film for LCD display with high stability, comprising the following steps:
[0020] S1: Prepare the thermosetting glue for the light absorption layer;
[0021] S2: Introduce the light absorption layer on the lower base film with a back coating;
[0022] S3: Sequentially introduce a lower prism structure layer and an upper base film on the light absorption layer;
[0023] S4: Introduce an upper prism structure layer on the upper surface of the upper base film;
[0024] S5: Introduce a light diffusion layer on the upper surface of the upper prism structure layer;
[0025] Or it comprises the following steps:
[0026] Step 1: Prepare the thermosetting glue for the light absorption layer;
[0027] Step 2: Sequentially introduce a lower prism structure layer and an upper base film on the lower base film with a back coating;
[0028] Step 3: Introduce the light absorption layer on the upper surface of the upper base film;
[0029] Step 4: Introduce an upper prism structure layer on the upper surface of the light absorption layer;
[0030] Step 5: Introduce a light diffusion layer on the upper surface of the upper prism structure layer.
[0031] Preferably, the specific process for preparing the thermosetting glue for the light absorption layer is as follows: The thermosetting glue includes a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant, and a silane coupling agent. Add each component into a container in sequence, stir and mix evenly to obtain the thermosetting glue; then add one or more light absorbers into the thermosetting glue, and stir evenly in an anhydrous and anaerobic environment to obtain the thermosetting glue for the light absorption layer;
[0032] The main agent is a sulfur- or mercapto-containing polyurethane, the auxiliary agent is a leveling agent; the diluent is an organic solvent; the silane coupling agent is a silane reagent with a mercapto group or a silane reagent with an amino group;
[0033] The mass ratio of the main agent to the diluent is 1:5 - 1:40, the mass percentage of the auxiliary agent in the main agent is 0.2% - 1.5%, the mass percentage of the curing agent in the main agent is 1% - 2%, the mass percentage of the antioxidant in the main agent is 0.2% - 0.5%, and the mass percentage of the silane coupling agent in the main glue is 0.01% - 0.08%;
[0034] The selection criteria of the light absorber are that the peak wavelength of its maximum absorption peak is 480nm-510nm or 570nm-610nm, and it can absorb light in other bands except the three-color light in the continuous spectrum; the mass ratio of the light absorber to the main agent is 0.001:100-5:100.
[0035] Further, the main agent is S-allyl thiopropionate, mercapto acrylate, mercapto methacrylate, mercapto aromatic acrylate, mercaptoethanol acrylate, 2-(2-naphthylthio)ethyl acrylate, 2-(2-naphthylthio)ethyl acrylate, 2-naphthylthioethyl acrylate, 2,2-dithiodiethanol diacrylate or 2,2-dithiodiethanol diacrylate;
[0036] The auxiliary agent is polyether polyester modified organic siloxane, polydimethyl siloxane, alkyl modified organic siloxane or terminal modified organic silicon;
[0037] The curing agent is aliphatic polyisocyanate, toluene diisocyanate, polyether diol, β-hydroxypropyl methacrylate, Sn 4+ Catalysts or inhibitors;
[0038] The diluent is one of ethyl acetate, cyclohexanone, butanone, or a mixture of two or more thereof;
[0039] The antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2-tert-butyl-4-hydroxybenzoic acid, tri-tert-butyl hydroxybenzoic acid, isopropyl diester, pentaerythritol tetra[β-propionate] ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, 1,3,5-trimethyl-2,4,6-triphenyl, dihydrazine, 2,2-oxalyl-bis[ethyl-3-]propionate, 2,2-oxalyl-bis[ethyl-3-]propionate, triethylene glycol diisocyanate, ... [3-propionate], 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid C7-C9 mixed esters, nonyl-N-(nonylphenyl)aniline, 2,6-di-tert-butyl-4-methylphenol, ascorbyl palmitate, tea polyphenols, tocopherol, flavonoids, butylated hydroxyanisole, butylated hydroxytoluene or tert-butylhydroquinone;
[0040] The silane coupling agent is 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, mercaptopropylsilane, 3-mercaptopropyltrimethylsilane, PSS-(3-mercapto)propyl-heptaisobutyl substitution, bis-[3-(triethoxysilyl)propyl]-tetrasulfide, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)trimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, diethylenetriaminepropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, n-butylaminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine, 3-(phenylamino)propyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, propyltrimethoxysilane or 3-(2-aminoethyl)-aminopropyltrimethoxysilane.
[0041] Further, the light absorber is a porphyrin compound coordinated with metal ions, and the structural formula is as follows:
[0042]
[0043] Wherein R1 and R2 are selected from H, OH, COOH, 1,2,3-trimethylbutanol group, phenyl, hexyl or phenol group; R3 is selected from H, phenyl or phenol group, and M is selected from Fe, Ni, Zn, Mn, Cu or Co.
[0044] Furthermore, the light absorber is hemin, copper phthalocyanine or manganese(III) tetraphenylporphyrin chloride, and their structural formulas are as follows:
[0045]
[0046] Preferably, the refractive index of the glue for the lower prism structure layer is 1.53 - 1.55, the bottom side length of the lower prism structure is 30 - 70 μm, and the included angle of the lower prism structure is 70 - 120°;
[0047] The base material of the upper base film or the lower base film is polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polymethyl methacrylate, triacetate cellulose, polyvinyl alcohol, polyethylene or polyvinylidene fluoride, and the thickness is 100 - 150 μm;
[0048] The refractive index of the glue for the upper prism structure layer is 1.48 - 1.51, the bottom side length of the upper prism structure is 30 - 70 μm, and the included angle of the upper prism structure is 70 - 120°; the upper lens structure is a hemispherical resin structure cured by acrylate glue, and the refractive index of the acrylate glue is 1.51 - 1.55.
[0049] Beneficial effects: (1) The optical composite film proposed by the present invention has the characteristics of filtering light, improving the color purity of transmitted light, and improving the brightness of transmitted light, and can improve the color gamut of LCD displays. Specifically:
[0050] An organic complex with a specific absorption range and a maximum absorption peak half-peak width less than 30nm is selected as a light absorber. When the white light in the backlight source passes through the light absorption layer, a specific spectral band (485-510nm, 580-610nm) in the continuous spectrum of white light is absorbed, while light in other bands dominated by blue, green and red light passes through the light absorption layer smoothly. Figure 1 As shown, the light absorption layer can effectively improve the color purity of the transmitted light and shorten the half-peak width of the three-color light, thereby achieving the purpose of improving the color gamut of the display;
[0051] (2) Improve the brightness of the filtered light, specifically:
[0052] The present invention absorbs the extra spectral bands in the white light source except the three-color light by selecting materials with specific absorption bands, thereby effectively improving the color purity of the transmitted light and the color gamut of the display; at the same time, the brightness loss caused by the absorption and filtering of light needs to be compensated by the brightness enhancement film;
[0053] Among conventional brightness enhancement films (such as prism films, prism composite films, reflective sheets, etc.), the prism composite film has the best brightness enhancement effect. In the present invention, a light absorption layer is coated below the prism structure in the prism composite film, and the filtered light source passes through the high-brightness prism structure and undergoes two light-collecting-light-emitting processes, so that its brightness is improved to a certain extent, effectively avoiding the problem of excessive brightness loss of the display caused by the introduction of the light absorption layer;
[0054] (3) Protect the core dye of the light absorbing layer and extend the service life of the film. Specifically:
[0055] The quantum dots or phosphor particles in the color gamut enhancement film that play a role in color gamut enhancement are likely to show poor reliability and short optical life in aging tests, thereby affecting the performance of the entire optical film. In the present invention, the light absorbing material is coated and dispersed on the inner coating of PET, and in the actual process, sulfur-containing polyurethane is added to the thermal curing glue containing the light absorber. The S element in the specific S-containing polyurethane compound can form coordination with the metal ions (Fe / Mn / Cu) in the porphyrin structure compound to generate interaction, thereby forming a protective effect on light absorption and extending its optical life. Figure 2 As shown; in addition, since the hydroxyl group in the hematoxylin molecule can react with the isocyanate in the polyurethane to form an amino iron complex, it can further promote the polymerization of the complex, improve the stability of the light absorber and the anti-aging performance of the entire film;
[0056] (4) Improve the peel strength between film layers. Specifically:
[0057] For a conventional optical composite film, the lower prism structure layer is directly introduced on the base film, and the peel strength mainly depends on the adhesiveness between the prism glue and the substrate. In the present invention, silica nanospheres are added to the lower prism glue, and a silane coupling agent is added to the light absorption layer. Through the chemical bonding of the silane coupling agent with the hydroxyl groups on the surface of the silica nanospheres, a siloxane compound is formed, as Figure 3 shown, thereby improving the peel strength between the lower prism layer and the substrate, and avoiding the problem of poor visual effect of the whole machine caused by delamination during processes such as cutting and assembly. At the same time, the silica nanospheres can act as diffusing particles and have a light scattering effect, further enhancing the product brightness;
[0058] (5) Avoid the problem of poor picture quality of conventional optical functional films (such as red dots, green dots, and white spots in QD films). Specifically:
[0059] In a conventional optical functional thin film, scattering particles are usually added to the glue layer, such as nanoscale titanium dioxide particles, nanoscale silica particles, or micron-scale silicone spheres. Usually, these scattering particles are prone to absorb moisture in the air and form agglomerates, resulting in "white spots"; in addition, quantum dot particles are also prone to agglomeration under the influence of the outside world and form "red dots" or "green dots", ultimately causing poor picture quality of the optical film under backlight. In the present invention, the selected light absorbers are all organic compounds, and the bonding glue / prism glue is composed of various organic solvents or organic resins. Therefore, the light absorbers have good solubility in the used glue, effectively avoiding the problem of uneven picture;
[0060] (6) Reduce the use of barrier films in the backlight module and reduce production costs. Specifically:
[0061] The selected organic light absorber in the present invention itself has good hydrophobicity and thermal stability, and the light absorption layer is also located between the prism structure and the PET substrate, further increasing the protection of the light absorber. Therefore, the requirement for the water and oxygen barrier properties of the selected substrate is very low, and ordinary substrates without barrier performance can be used; in addition, the structure of the filter film in the present invention integrates functions such as diffusion, brightness enhancement, color gamut improvement, and color purity improvement, thinning the backlight module architecture and reducing the production and assembly costs. Description of the Drawings
[0062] Figure 1 is a schematic diagram of the spectrum emitted by the backlight of an ordinary LCD monitor. Among them, the backlight uses YAG powder, and data is collected using a CA410 color analyzer. The main function of the light absorber in the filter film is to absorb light with wavelengths of 480 - 510 nm and 570 - 610 nm;
[0063] Figure 2Schematic diagram of the mechanism of action between the light absorber and the additive in the light absorption layer of the present invention;
[0064] Figure 3 Schematic diagram of the mechanism of action between the silane reagent in the light absorption layer of the present invention and the silica nanospheres in the lower prism structure layer. In Figure A, 3-aminopropyltrimethoxysilane is taken as an example, which is hydrolyzed and bonded to the silica nanospheres to form characteristic products and characteristic structures; in Figure B, 3-mercaptopropyltrimethoxysilane is taken as an example, which is hydrolyzed and bonded to the silica nanospheres to form characteristic products and characteristic structures;
[0065] Figure 4 Schematic diagram of Structure 1 of the high-stability filter film for LCD display of the present invention;
[0066] Figure 5 Schematic diagram of Structure 2 of the high-stability filter film for LCD display of the present invention;
[0067] Figure 6 Schematic diagram of Structure 3 of the high-stability filter film for LCD display of the present invention;
[0068] Figure 7 Schematic diagram of Structure 4 of the high-stability filter film for LCD display of the present invention;
[0069] Figure 8 Schematic diagram of the preparation process of Structure 3 of the high-stability filter film for LCD display of the present invention;
[0070] Figure 9 Schematic diagram of the backlight application architecture of Structure 3 of the high-stability filter film for LCD display of the present invention;
[0071] Numbers in the figure: 1. Light diffusion layer, 2. Upper prism structure layer, 3. Upper base film, 4. Lower prism structure layer, 5. Light absorption layer, 6. Lower base film, 7. Back coating, 8. Upper lens structure layer. Detailed implementation manners
[0072] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments:
[0073] Example 1
[0074] As Figure 4 shown, a high-stability filter film for LCD display includes, from bottom to top, a back coating 7, a lower base film 6, a light absorption layer 5, a lower prism structure layer 4, an upper base film 3, and an upper prism structure layer 2. Its preparation method includes the following steps:
[0075] S1. Prepare the thermosetting glue for the light absorption layer. Specifically:
[0076] The heat-curing glue comprises a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant and a silane coupling agent. Each component is sequentially added into a container, and after stirring and mixing evenly, the heat-curing glue is obtained; then a light absorber is added into the heat-curing glue, and after stirring evenly in an anhydrous and oxygen-free environment, the heat-curing glue for the light absorption layer is obtained.
[0077] The above-mentioned main agent (main glue) is S-allyl thioacrylate, the auxiliary agent is a polyether-polyester modified silicone oxygen alkane, the curing agent is β-hydroxypropyl methacrylate, and the diluent is ethyl acetate and methyl ethyl ketone (the mass ratio of the two is 4:2); the antioxidant is dibutylhydroxytoluene; the silane coupling agent is 3-aminopropylmethyldiethoxysilane.
[0078] The mass ratio of the main agent to the diluent is 1:20. The mass percentage of the auxiliary agent in the main glue is 0.2%, the mass percentage of the curing agent in the main glue is 1%, the mass percentage of the antioxidant in the main glue is 0.2%, and the mass percentage of the silane coupling agent in the main glue is 0.01%.
[0079] The above-mentioned light absorber is hemin, and its mass ratio to the main agent of the heat-curing glue is 0.001:100.
[0080] S2. Introduce the light absorption layer 5 on the lower base film 6 with a back coating 7. Specifically:
[0081] Connect the heat-curing glue for the light absorption layer prepared in step S1 to the glue supply system of the equipment, and coat it on the flat lower base film 6 by means of microgravure coating, knife coating, dipping or spraying. Then, pass it through a high-temperature oven at 80 °C to remove the organic solvent, and form a thin and uniform light absorption layer 5 on the lower base film 6. Wind it up, and store the coil in a drying room at 60 °C for 24 h for curing and then use it. The lower base film 6 is a PET film with a thickness of 50 μm. It only requires that the surface of the lower base film is flat, without MD lines and TD lines, and the light transmittance is required to be above 90%.
[0082] S3. Sequentially introduce the lower prism structure layer 4 and the upper base film 3 on the light absorption layer 5. Specifically:
[0083] Silica nanospheres are introduced into the prism glue, and after stirring at 200 rpm / min, the glue for the lower prism structure layer is obtained. The prism glue uses commercial UV acrylate. The silica nanospheres can be prepared by the sol-gel method, with a particle size of 300 nm and a proportion of 0.02% in the glue for the lower prism structure layer. A steel roller with a specific structure and angle is selected, and through UV curing transfer structure, the lower prism structure layer 4 is introduced onto the light absorption layer 5 and bonded to the upper base film 3. The refractive index of the glue for the lower prism structure layer is 1.53, the bottom side length of the lower prism structure is 30 μm, and the included angle of the lower prism structure is 70°; the upper base film 3 is a PET film with a thickness of 100 μm, and only requires the surface of the upper base film to be flat, without MD lines and TD lines, and the light transmittance to be above 90%.
[0084] S4. Introduce the upper prism structure layer 2 on the upper surface of the upper base film 3. Specifically:
[0085] By selecting a steel roller or a soft film with a specific structure and through UV curing transfer structure, the upper prism structure layer 2 is introduced onto the upper base film 3. The refractive index of the glue for the upper prism structure layer is 1.48, the bottom side length of the upper prism structure is 30 μm, the included angle of the upper prism structure is 70 - 120°, and the upper prism structure layer and the lower prism structure layer are arranged in a +90° rotation.
[0086] Example 2
[0087] As Figure 5 shown, a high-stability filter film for LCD display includes, from bottom to top, a back coating 7, a lower base film 6, a light absorption layer 5, a lower prism structure layer 4, an upper base film 3, and an upper lens structure layer 8. Its preparation method includes the following steps:
[0088] S1. Prepare the thermosetting glue for the light absorption layer. Specifically:
[0089] The thermosetting glue includes a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant, and a silane coupling agent. Each component is added to a container in sequence, and after stirring and mixing evenly, the thermosetting glue is obtained; then the light absorber is added to the thermosetting glue and stirred evenly in an anhydrous and anaerobic environment to obtain the thermosetting glue for the light absorption layer.
[0090] The above main agent is mercapto methacrylate, the auxiliary agent is polydimethylsiloxane, the curing agent is aliphatic polyisocyanate, the diluent is ethyl acetate, the antioxidant is ascorbyl palmitate; the silane coupling agent is 3-mercaptopropyltrimethoxysilane.
[0091] The mass ratio of the main agent to the diluent is 1:30. The mass percentage of the auxiliary agent in the main glue is 0.5%, the mass percentage of the curing agent in the main glue is 1.5%, the mass percentage of the antioxidant in the main glue is 1%, and the mass percentage of the silane coupling agent in the main glue is 0.05%.
[0092] The above light absorber is copper phthalocyanine, and its mass ratio to the main agent of the thermosetting glue is 1:100.
[0093] S2. Introduce the light absorption layer 5 on the lower base film 6 with the back coating 7. Specifically:
[0094] Connect the light absorption layer thermosetting glue prepared in step S1 to the glue supply system of the equipment, and coat it on the flat lower base film 6 by microgravure coating, knife coating, dipping or spraying. Then, pass it through a high-temperature oven at 100°C to remove the organic solvent, form a thin and uniform light absorption layer 5 on the lower base film 6, wind it up, and store the coil in a 60°C drying room for 24 hours for curing and standby. The lower base film 6 is a PC film with a thickness of 100 μm. It only requires that the surface of the lower base film is flat, without MD lines and TD lines, and the light transmittance is required to be above 90%.
[0095] S3. Sequentially introduce the lower prism structure layer 4 and the upper base film 3 on the light absorption layer 5. Specifically:
[0096] Introduce silica nanospheres into the prism glue, and obtain the lower prism structure layer glue after high-speed stirring (500 rpm / min). The prism glue uses commercial UV acrylate. The silica nanospheres can be prepared by the sol-gel method, with a particle size of 100 - 300 nm, accounting for 1% of the mass of the lower prism structure layer glue. Select a steel roller with a specific structure and angle, and introduce the lower prism structure layer 4 on the light absorption layer 5 and bond it with the upper base film 3 through UV curing transfer. The refractive index of the lower prism structure layer glue is 1.55, the bottom side length of the lower prism structure is 60 μm, and the included angle of the lower prism structure is 90°; the upper base film 3 is a polyethylene naphthalate film with a thickness of 100 μm. It only requires that the surface of the upper base film is flat, without MD lines and TD lines, and the light transmittance is required to be above 90%;
[0097] S4. Introduce the upper lens structure layer 8 on the upper surface of the upper base film 3. Specifically: The upper lens structure is a hemispherical resin structure, cured from acrylate glue, and the refractive index of the acrylate glue is 1.55.
[0098] Example 3
[0099] As Figure 6As shown in the figure, a light filtering film for LCD display with high stability includes, from bottom to top, a back coating 7, a lower base film 6, a light absorption layer 5, a lower prism structure layer 4, an upper base film 3, an upper prism structure layer 2, and a light diffusion layer 1. Its preparation method is as follows Figure 8 shown, and includes the following steps:
[0100] S1. Prepare the thermosetting glue for the light absorption layer. Specifically:
[0101] The thermosetting glue includes a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant, and a silane coupling agent. Each component is added into a container in sequence. After stirring and mixing evenly, the thermosetting glue is obtained; then the light absorbent is added into the thermosetting glue, and it is stirred evenly under an anhydrous and anaerobic environment to obtain the thermosetting glue for the light absorption layer;
[0102] The above-mentioned main agent is mercapto aromatic acrylate, the auxiliary agent is alkyl-modified organosiloxane, the curing agent is β-hydroxypropyl methacrylate, the diluent is ethyl acetate and cyclohexanone, and the mass ratio of ethyl acetate to cyclohexanone is 5:2. The antioxidant is ascorbyl palmitate; the silane coupling agent is 3-mercaptopropylmethyldimethoxysilane;
[0103] The mass ratio of the main agent to the diluent is 1:5. The mass percentage of the auxiliary agent in the main glue is 1%, the mass percentage of the curing agent in the main glue is 1.5%, the mass percentage of the antioxidant in the main glue is 0.3%, and the mass percentage of the silane coupling agent in the main glue is 0.08%;
[0104] The above-mentioned light absorbent is manganese (II) meso-tetraphenylporphyrin chloride, and its mass ratio to the main agent of the thermosetting glue is 2:100.
[0105] S2. Introduce the light absorption layer 5 on the lower base film 6 with the back coating 7. Specifically:
[0106] Connect the thermosetting glue for the light absorption layer prepared in step S1 to the glue supply system of the equipment, and coat it on the flat lower base film 6 by microgravure coating, knife coating, dipping or spraying. Then, pass it through a high-temperature oven at 110°C to remove the organic solvent, and form a thin and uniform light absorption layer 5 on the lower base film 6. Wind it up, and store the coil in a drying room at 60°C for 24 hours for curing and then set aside. The lower base film 6 is a polycarbonate film with a thickness of 100 μm. It only requires that the surface of the lower base film is flat, without MD texture and TD texture, and the light transmittance is required to be above 90%.
[0107] S3. Introduce the lower prism structure layer 4 and the upper base film 3 on the light absorption layer 5 in sequence. Specifically:
[0108] Silica nanospheres are introduced into the prism glue, and after stirring at a high speed (1000 rpm / min), the glue for the lower prism structure layer is obtained. The prism glue uses commercial UV acrylate. The silica nanospheres can be prepared by the sol-gel method, with a particle size of 200 nm and a mass ratio of 0.08% in the glue for the lower prism structure layer. A steel roller with a specific structure and angle is selected, and through the UV curing transfer structure, the lower prism structure layer 4 is introduced onto the light absorption layer 5 and bonded to the upper base film 3. The refractive index of the glue for the lower prism structure layer is 1.53, the bottom side length of the lower prism structure is 60 μm and 70 μm at intervals, and the included angle of the lower prism structure is 120°; the upper base film 3 is a triacetate cellulose film with a thickness of 100 μm, and only requires that the surface of the upper base film is flat, without MD lines and TD lines, and the light transmittance is required to be above 90%.
[0109] S4. Introduce the upper prism structure layer 2 on the upper surface of the upper base film 3. Specifically:
[0110] By selecting a steel roller or a soft film with a specific structure, through the UV curing transfer structure, the upper prism structure layer 2 is introduced onto the upper base film 3. The refractive index of the glue for the upper prism structure layer is 1.55, the bottom side length of the upper prism structure is 60 μm, the included angle of the upper prism structure is 100°, and the upper prism structure layer and the lower prism structure layer are arranged in a +90° rotation.
[0111] S5. Introduce the light diffusion layer 1 on the upper surface of the upper prism structure layer 2. Specifically:
[0112] Prepare the diffusion layer glue: A polyurethane glue containing urethane groups and isocyanate groups is uniformly dispersed in ethyl acetate by stirring at a speed of 100 rpm / min; the mass ratio of the polyurethane glue to ethyl acetate is 1:10;
[0113] Polyamide particles with particle sizes of 6 - 8 μm and 10 - 12 μm are dispersed in the ethyl acetate solution of the above polyurethane glue. Specifically, the two different particle size polyamide particles are mixed according to a mass ratio of (2 - 6):(1 - 3), and then dispersed in the polyurethane glue. Among them, the total mass of the diffusion particles (polyamide particles) accounts for 0.02% of the polyurethane glue. Finally, through the thermal curing process, the diffusion particles are introduced onto the polyethylene terephthalate base film.
[0114] As Figure 9As shown in the figure, the application scenario of the filter film prepared in this embodiment is that the backlight source is a backlight source composed of white YAG powder and a white light source mixed with KSF powder; this optical film is placed between the backlight source and the TFT-LCD glass. The advantage is that it can be directly applied to the LCD backlight module, only replacing the brightness enhancement film in the original architecture, without the need to readjust the structure of the backlight module, and it has no impact on other existing components such as TFT-LCD, and can be directly mass-produced.
[0115] Example 5
[0116] As Figure 7 shown, a filter film for LCD display with high stability includes, from bottom to top, a back coating 7, a lower base film 6, a lower prism structure layer 4, an upper base film 3, a light absorption layer 5, an upper prism structure layer 2, and a light diffusion layer 1. Its preparation method includes the following steps:
[0117] S1. Prepare the thermosetting glue for the light absorption layer. Specifically:
[0118] The thermosetting glue includes a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant, and a silane coupling agent. Add each component into a container in sequence, stir and mix evenly to obtain the thermosetting glue; then add the light absorber into the thermosetting glue and stir evenly in an anhydrous and oxygen-free environment to obtain the thermosetting glue for the light absorption layer;
[0119] The above-mentioned main agent is 2,2-dithiodiethanol diacrylate, the auxiliary agent is polyether-polyester modified silicone oxygen, the curing agent is polyether diol, the diluent is ethyl acetate, cyclohexanone, and butanone, and the mass ratio of ethyl acetate: cyclohexanone: butanone is 6:2:1. The antioxidant is tribenzylhydroxybenzoic acid; the silane coupling agent is 3-aminopropyltriethoxysilane;
[0120] The mass ratio of the main agent to the diluent is 1:20. The mass fraction of the auxiliary agent in the main glue is 0.4%, the mass fraction of the curing agent in the main glue is 1%, the mass fraction of the antioxidant in the main glue is 0.2%, and the mass fraction of the silane coupling agent in the main glue is 0.02%;
[0121] The above-mentioned light absorber is hematin and iron oxide nanoparticles with a diameter of 50-200 nm. The mass ratio of hematin, iron oxide to the main agent of the thermosetting glue is 1:0.1:5000.
[0122] S2. Sequentially introduce the lower prism structure layer 4 and the upper base film 3 on the lower base film 6 with the back coating 7. Specifically:
[0123] Silica nanospheres are introduced into the prism glue, and the glue for the lower prism structure layer is obtained after stirring at a high speed (500 rpm / min). The prism glue uses commercial UV acrylate. The silica nanospheres can be prepared by the sol-gel method, with a particle size of 100 nm and a mass ratio of 0.02% in the glue for the lower prism structure layer. A steel roller with a specific structure and angle is selected, and through the UV curing transfer structure, the lower prism structure layer 4 is introduced onto the lower base film 6 and bonded to the upper base film 3. The refractive index of the glue for the lower prism structure layer is 1.53, the bottom side length of the lower prism structure is 50 μm, and the included angle of the lower prism structure is 70 - 120°; the upper base film 3 is a polycarbonate film with a thickness of 100 - 150 μm, and the lower base film 6 is a polyethylene terephthalate film with a thickness of 100 μm. It is only required that the surfaces of the upper and lower base films are flat, without MD and TD patterns, and the light transmittance is required to be above 90%.
[0124] S3. Introduce the light absorption layer 5 onto the upper base film 3. Specifically:
[0125] Connect the thermosetting glue of the light absorption layer prepared in step S1 to the glue supply system of the equipment, and coat it on the flat upper base film 3 by means of microgravure coating, knife coating, dipping or spraying. Then, through a high-temperature oven at 100 °C, the organic solvent is removed, and a thin and uniform light absorption layer 5 is formed on the upper base film 3. Wind it up, and store the coil in a drying room at 60 °C for 24 h for aging and then reserve it for use.
[0126] S4. Introduce the upper prism structure layer 2 onto the upper surface of the light absorption layer 5. Specifically:
[0127] By selecting a steel roller or a soft film with a specific structure, through the UV curing transfer structure, the upper prism structure layer 2 is introduced onto the light absorption layer 5. The refractive index of the glue for the upper prism structure layer is 1.55, the bottom side length of the upper prism structure is 50 μm, and the included angle of the upper prism structure is 100°.
[0128] S5. Introduce the light diffusion layer 1 onto the upper surface of the upper prism structure layer 2. Specifically:
[0129] Prepare the diffusion layer glue: A polyurethane glue containing urethane groups and isocyanate groups is uniformly dispersed in ethyl acetate by stirring at a rotation speed of 100 rpm / min; the mass ratio of the polyurethane glue to ethyl acetate is 1:10;
[0130] Disperse polyamide particles with particle sizes of 6 - 8 μm and 10 - 12 μm in the ethyl acetate solution of the above polyurethane glue. Specifically, mix two polyamide particles with different particle sizes according to a mass ratio of (2 - 6):(1 - 3), and then disperse them in the polyurethane glue. Among them, the total mass of the diffusion particles (polymethyl methacrylate particles) accounts for 0.02% of the polyurethane glue. Finally, introduce the diffusion particles onto the polyethylene terephthalate base film through a thermal curing process.
[0131] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A filter film for LCD display with high stability, characterized in that: It includes a back coating (7), a lower base film (6), a light absorption layer (5), a lower prism structure layer (4) and an upper base film (3). When the light absorption layer (5) is located on the upper surface of the lower base film (6), the structure of the filter film includes, from bottom to top, a back coating (7), a lower base film (6), a light absorption layer (5), a lower prism structure layer (4) and an upper base film (3) in sequence, and an upper prism structure layer (2) or an upper lens structure layer (8) is provided on the upper surface of the upper base film (3); When the light absorption layer (5) is located on the upper surface of the upper base film (3), the structure of the filter film includes, from bottom to top, a back coating (7), a lower base film (6), a lower prism structure layer (4), an upper base film (3) and a light absorption layer (5) in sequence, and an upper prism structure layer (2) or an upper lens structure layer (8) is provided on the upper surface of the light absorption layer (5).
2. A high-stability filter film for LCD display according to claim 1, characterized in that: It further includes a light diffusion layer (1), and the light diffusion layer (1) is provided on the upper surface of the upper prism structure layer (2).
3. A method for preparing a filter film for LCD display with high stability as described in claim 1, characterized in that, When the light absorption layer (5) is located on the upper surface of the lower base film (6), the preparation method of the filter film includes the following steps: S1. Prepare the thermosetting glue for the light absorption layer; S2. Introduce the light absorption layer (5) onto the lower base film (6) with a back coating (7); S3. Sequentially introduce the lower prism structure layer (4) and the upper base film (3) onto the light absorption layer (5); S4. Introduce the upper prism structure layer (2) or the upper lens structure layer (8) onto the upper surface of the upper base film (3).
4. A method for preparing a filter film for LCD display with high stability as claimed in claim 1, characterized in that, When the light absorption layer (5) is located on the upper surface of the upper base film (3), the preparation method of the filter film includes the following steps: Step 1. Prepare the thermosetting glue for the light absorption layer; Step 2. Sequentially introduce the lower prism structure layer (4) and the upper base film (3) onto the lower base film (6) with a back coating (7); Step 3. Introduce the light absorption layer (5) onto the upper surface of the upper base film (3); Step 4. Introduce the upper prism structure layer (2) or the upper lens structure layer (8) onto the upper surface of the light absorption layer (5).
5. A method for preparing a filter film for LCD display with high stability according to claim 2, characterized in that, It includes the following steps: S1. Prepare the thermosetting glue for the light absorption layer; S2. Introduce the light absorption layer (5) onto the lower base film (6) with a back coating (7); S3. Sequentially introduce the lower prism structure layer (4) and the upper base film (3) onto the light absorption layer (5); S4. Introduce the upper prism structure layer (2) onto the upper surface of the upper base film (3); S5. Introduce the light diffusion layer (1) onto the upper surface of the upper prism structure layer (2); Or it includes the following steps: Step 1. Prepare the thermosetting glue for the light absorption layer; Step 2. Sequentially introduce the lower prism structure layer (4) and the upper base film (3) onto the lower base film (6) with a back coating (7); Step 3. Introduce the light absorption layer (5) onto the upper surface of the upper base film (3); Step 4. Introduce the upper prism structure layer (2) onto the upper surface of the light absorption layer (5); Step 5. Introduce the light diffusion layer (1) onto the upper surface of the upper prism structure layer (2).
6. The preparation method according to any one of claims 3-5, characterized in that, The specific process for preparing the thermosetting glue for the light absorption layer is as follows: The thermosetting glue includes a main agent, an auxiliary agent, a curing agent, a diluent, an antioxidant, and a silane coupling agent. Each component is added to a container in sequence, and after stirring and mixing evenly, the thermosetting glue is obtained; then one or more light absorbers are added to the thermosetting glue, and it is stirred evenly in an anhydrous and oxygen-free environment to obtain the thermosetting glue for the light absorption layer; The main agent is a sulfur- or mercapto-containing polyurethane, the auxiliary agent is a leveling agent; the diluent is an organic solvent; the silane coupling agent is a mercapto-containing silane reagent or an amino-containing silane reagent; The mass ratio of the main agent to the diluent is 1:5 - 1:40, the mass percentage of the auxiliary agent in the main agent is 0.2% - 1.5%, the mass percentage of the curing agent in the main agent is 1% - 2%, the mass percentage of the antioxidant in the main agent is 0.2% - 0.5%, and the mass percentage of the silane coupling agent in the main glue is 0.01% - 0.08%; The selection criterion for the light absorber is that the peak wavelength of its maximum absorption peak is 480nm - 510nm or 570nm - 610nm, and it can absorb light in other bands in the continuous spectrum except for the three primary colors of light; the mass ratio of the light absorber to the main agent is 0.001:100 - 5:
100.
7. The preparation method according to claim 6, wherein: The main agent is S-allyl thionopropionate, mercaptoacrylate, mercaptomethylacrylate, mercaptoaromatic acrylate, mercaptoethanol acrylate, 2-(2-naphthylthio)ethyl acrylate, 2-(2-naphthylthio)ethyl acrylate, 2-naphthylethylthio acrylate, 2,2-dithiodiethanol diacrylate or 2,2-dithiodiethanol diacrylate; The auxiliary agent is a polyether-polyester modified silicone, polydimethylsiloxane, an alkyl-modified silicone, or a terminally modified silicone; The curing agent is aliphatic polyisocyanate, toluene diisocyanate, polyether diol, β-hydroxypropyl methacrylate, Sn 4+ catalyst or inhibitor; The diluent is one of ethyl acetate, cyclohexanone, and methyl ethyl ketone, or a mixture of two or more of them; The antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2-tert-butyl-4-hydroxybenzoic acid, tri-tert-butylhydroxybenzoic acid, isopropyl (2-hydroxybenzoic acid) diester, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl 3,5-di-tert-butyl-4-hydroxyphenylpropionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-tert-butyl-4-hydroxybenzoyl)hydrazine, 2,2-oxamido-bis[ethyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)]propionate, 2,2-oxamido-bis[ethyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)]propionate, triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, C7-C9 mixed esters of 3,5-di-tert-butyl-4-hydroxybenzenepropanoic acid, nonyl-N-(nonylphenyl)aniline, 2,6-di-tert-butyl-4-methylphenol, ascorbyl palmitate, tea polyphenols, tocopherol, flavonoids, butylated hydroxyanisole, dibutylhydroxytoluene or tert-butylhydroquinone; The silane coupling agent is 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, mercaptopropylsilane, 3-mercaptopropyltrimethylsilane, PSS-(3-mercapto)propyl-hepta-isobutyl substituted, bis-[3-(triethoxysilyl)propyl]-tetrasulfide, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)trimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, diethylenetriaminepropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, n-butylaminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine, 3-(phenylamino)propyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, propyltrimethoxysilane or 3-(2-aminoethyl)-aminopropyltrimethoxysilane.
8. The preparation method according to claim 6, characterized in that: The light absorber is a porphyrin compound coordinated with metal ions, and the structural formula is as follows: Wherein R1 and R2 are selected from H, OH, COOH, 1,2,3-trimethylbutanol group, phenyl, hexyl or phenol group; R3 is selected from H, phenyl or phenol group, and M is selected from Fe, Ni, Zn, Mn, Cu or Co.
9. The preparation method according to claim 8, characterized in that: The light absorber is hemin, copper phthalocyanine or manganese(III) tetraphenylporphyrin chloride, and their structural formulas are as follows:
10. The preparation method according to any one of claims 3-5, characterized in that: The refractive index of the glue of the lower prism structure layer is 1.53 - 1.55, the bottom side length of the lower prism structure is 30 - 70 μm, and the included angle of the lower prism structure is 70 - 120°; The base material of the upper base film (3) or the lower base film (6) is polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polymethyl methacrylate, triacetate cellulose, polyvinyl alcohol, polyethylene or polyvinylidene fluoride, and the thickness is 100 - 150 μm; The refractive index of the glue of the upper prism structure layer is 1.48 - 1.51, the bottom side length of the upper prism structure is 30 - 70 μm, and the included angle of the upper prism structure is 70 - 120°; the upper lens structure is a hemispherical resin structure cured by acrylate glue, and the refractive index of the acrylate glue is 1.51 - 1.55.